Pengaruh Model Pembelajaran Examples Non Examples terhadap Kemampuan Menulis Surat Resmi pada Siswa Kelas VIII SMP Negeri 1 Bojong, Pandeglang - Sauri, Sopyan (Jurnal Artikula, 2018)
The purpose of this study is to investigate the influence of examples non examples learning model on the ability to write an official letter of eighth grade students of SMP Negeri 1 Bojong Academic Year 2015/2016. This study uses an experimental method conducted from April to May, white a population of this research is all class VIII SMP Negeri 1 Bojong students in the academic year 2015/2016. The sample technique used is cluster random sampling, so that from the sampling technique the sample obtained is the class VIII B and class VIII A. Each of them is 28 students. So the overall sample is 56 samples. The VIII B class was given treatment in the form of the use of examples non examples learning model. Whereas class VIII A used an expository learning model in the learning process. Based on the results of data processing, it was obtained an illustration that the students’ official letter writing skill using the examples non examples learning model in the experimental class was quite good. It could be seen from 28 students, there are 20 students or 71.41% who get score more than 68. While the rest 8 students or 28.56% got a score between 50-67 by an average score of 71.78; highest value 83, and lowest value 50. While the students’ official letter writing skill using the expository learning model is not good. As illustrated by 28 students who were sampled, there were 10 students or 35.7% got more than 54. While the remaining 18 students or 64.27% got scores between 30-53. by an average score of 51.35; the highest value is 64, and the lowest value is 30. Thus, it can be concluded that there is a positive influence on the use of examples non examples learning model on the ability to write an official letter for eighth grade students of SMP Negeri 1 Bojong academic year 2015/2016.